A Smart Commercial Transport Platform-Tranzo - Sayyad, G. G.; Bhosale, Vishwajit; Deshmukh, Aniket; Barge, Yash; Dange , Fardin (International Journal of Recent Advances in Engineering and Technology, 2025)
The commercial transport and logistics sector faces fragmentation, opaque pricing, under-utilized fleets, and lack of reliable tracking. Existing passenger-focused ride-hailing platforms have transformed passenger mobility but do not fully meet heavy-vehicle and commercial freight needs. This survey reviews techniques and technologies relevant for building an intelligent commercial vehicle booking platform — Tranzo — that integrates Artificial Intelligence (AI), Machine Learning (ML), Cloud infrastructure, GPS tracking, secure payments, and recommendation/dynamic-pricing engines. We summarize related work in dynamic pricing, fleet allocation, IoT and sensor integration, blockchain-based payments, and GPS/route optimization; identify key research gaps; describe Tranzo’s proposed architecture and modules; and discuss expected outcomes and comparisons with existing solutions. The survey shows that an integrated AI/ML + cloud + GPS platform can significantly improve transparency, utilization, and reliability in commercial transport.